Synthesis of anthrose lipidic derivative as mimic of B. anthracis BclA glycoprotein for use in ELISA-like binding assays. Issue 2 (12th February 2016) - Jakas, Andreja; Perc, Milica; Suć, Josipa; Rodriguez, Maria C.; Cudic, Mare; Cudic, Predrag
ABSTRACT: The surfaces of Bacillus anthracis endospores expose anthrose-containing oligosaccharides, which have been considered for use as a target for specific detection of the spores. In this direction, we have developed an efficient and straightforward synthetic strategy toward anthrose lipidic derivate tetradecyl 4, 6-dideoxy-4-(3-hydroxy-3-methylbutanamido)-2- O -methyl-β-d -glucopyranoside16 as a model target for B. anthracis spores. The ability of the prepared anthrose and glucose (for control purposes) lipidic derivatives to display on a multiwell plate was demonstrated by a colorimetric phenol-sulfuric acid assay and their potential utility in multiwell binding assays was assessed using fluorescein-labeled concanavalin A (ConA-FITC) and Aleuria aurantia (AAL-FITC). GRAPHICAL ABSTRACT: